Supersegmental Possibilities of Pause in English and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern linguistics, phonopragmatics is a new branch that examines both segmental and suprasegmental units, such as intonation, stress, rhythm, and pauses, play a crucial role in conveying meaning and value in speech in both English and Uzbek languages. These elements are essential for expressing emotions, attitudes, emphasis, and other nuances in communication. The use of pauses is a key element of prosody, and speakers can use pauses to convey positive or negative implications in various language contexts. The author provides factual and analytical discussions on the use of pauses, comparing English and Uzbek languages.